Case Report: Vasospastic angina presenting as phantom odor perception - Zubair, Haroon; Suma, Valentin; Masood, Faisal; Jan, M. Fuad; Bajwa, Tanvir; Haddadian, Babak (Frontiers in Cardiovascular Medicine, 2024)
We present a rare case of vasospastic angina presenting with symptoms of phantom odor perception. Symptoms of angina are usually described as chest pain or shortness of breath. We present a rare case of olfactory hallucination as angina equivalent. This is educational and interesting to note for cardiologists as there should be a high index of suspicion for underlying coronary artery disease when a patient mentions such complaints. Similar symptoms in our patient along with electrocardiographic and echocardiographic features provide insight into this rare presentation of vasospastic angina.